APLICATION OF HIGH CONSTANT-TEMPERATURE OVEN METHOD AND INTACT SEED UTILIZATION ON DETERMINING SEED MOISTURE CONTENT OF OIL PALM (Elaeis guineensis L. Jacq.) - Arif, Mohamad; Illahi, Nur Muhammad Akbar (Jurnal Penelitian Kelapa Sawit, 2018)
Seed moisture content is a crucial factor which will determine seed viability during storage and influence successful germination process. By that reason, ability to measure seed moisture content in precise is a basic need for seed producers. For plant species which produces large seeds such as oil palm, International Seed Testing Association (ISTA) demands that seed moisture content can be determined by using high or low constant oven temperature with seeds been sliced or crushed before the oven application. On the other hand, seed producers commonly use intact seeds to determine the parameters. Test results to compare between the two methods showed that low constant oven temperature generated higher seed moisture content than that of the high constant oven temperature method. In addition, moisture contents, which were generated by intact and crushed seeds, were not significantly different. Based on seed component, kernel contained higher moisture than shell, both by utilizing low and high constant oven temperature. Further research is needed due to a large range of shell thickness of oil palm seeds.